Review of the impact of technology use on modern painting / Izaddin Matrahah, Zakiah Mohamed and Muhammad Salehuddin Zakaria - Matrahah, Izaddin; Mohamed, Zakiah; Zakaria, Muhammad Salehuddin (Faculty of Art and Design, 2025)
In the 21st century, technology has profoundly reshaped the world of art, including the domain of modern painting. From digital tools to Artificial Intelligence (AI) driven innovations, the intersection of art and technology has opened new possibilities, redefined traditional techniques, and expanded creative boundaries. This study uses qualitative methods according to a conceptual framework such as environmental visual analysis, visual studies, evaluation of visual technology, review of technical effects, study into the effects of technology on the past, and historical technology. In this study, the discussion is based on a new movement that has made an impact in the world of modern art and has had a big effect on all kinds of creativity. Another big reason for this new age of New Modern art is the progress made in computer technology. Researchers, artists, and even art lovers have been able to find new ways to make art with its help. Lastly, modern painting is seen as a major step forward in the history of the fine arts. It has opened a new chapter in the world of visual art, which is made better using technology in works. There were a lot of new ideas in New Modern Painting. Some radical ideas have been made better, like site-specific art, installation art, low-brow art, and digital art. These new ideas are now backed up by technology, like computers, all kinds of electronic gadgets, and digital publications.